Aspectos tectónicos con relación a la geología local en el sector de k´uypan en Ocopata un estudio de caso - Puma, Yessenia (2019)
The objective of this research work was to determine the local geology and its tectonic influence of the K´uypan Occopata Cusco sector that presented sedimentary sequences of the Puquin, Chilca, Quilque and Kayra Formations, of which it was determined at a scale of 1 / 5500 the inferred contacts, due to the high tectonism within the study area and the abrupt change in lithology. To understand the structural part of the K'uypan sector, the study of satellite images was carried out to understand the dynamics and regional structural control that is of great importance for the interpretation of the different geological and tectonic events, then in the field it was corroborated with the local geological-structural mapping, where it was possible to observe the structural controls in the NW-SE direction with greater predominance in the place, as well as normal, inverse, synextral and dextral faults.